Actividades de germoplasma de frijol. Recolección de germoplasma, multiplicación y distribución - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
The status of the Phaseolus collection held at the CIAT Genetic Resources Unit and the results of germplasm explorations in 1985 are presented in table form. Future plans include collection activities through expeditions in the Andean region. (CIAT)